PROMISING ACCESSIONS OF CHAENOMELES AND THEIR USE IN THE FUNCTIONAL FOOD - V. N. Sorokopudov; O. A. Sorokopudova; A. G. Kuklina; A. В. Artjukhova; N. I. Myachikova (Овощи России, 2018)
A complex analysis is crucial for obtaining new resistant varieties and developing recommendations for the use of the fruit of Chaenomeles. The task of this study was to assess the productivity and quality of the fruit of the selected forms of Chaenomeles in Central Russia, with the determination of the possibility of a no-waste technology for fruit processing, and the appropriateness of using functional food in the composition of products. The studies were conducted in 2012-2016. In the Botanical Gardens of the National Research University "BelGU" (Belgorod), in the FGBNU VSTISP and GBS N.V. Tsitsina. As materials for the study, 6 selective forms of Chaenomeles, obtained from free pollination of the ‘Calif’ variety, used as a control, were used. The study was carried out according to the generally accepted methodology of varietal studies, along with using the authors' methodical development. A sufficiently high nutritional and biological value of the chelating of the Chaenomeles fruit has been observed. At the same time, the minerals, carbohydrates and vitamins from entire fruits exceed the content of ones squeezed from the pulp. The obtained results of the studies allow us to conclude that it is advisable to organize a non-waste technology for the processing of fruit of Chaenomeles, which can serve as one of the components for the enrichment of food products. Thus, a comprehensive assessment of the biological properties and productivity of breeding forms of Chaenomeles has been made showing that they exceeded the parent variety in stability are regarded as promising intense-vitamin fruit culture, that can be used for various processing methods, as part of functional and therapeutic product-prophylactic nutrition, especially in obtaining natural low-calorie foods.